Discretion on the Frontline: The Street Level Bureaucrat in English Statutory Homelessness Services. Issue 1 (16th September 2014) - Alden, Sarah
Abstract : This article employs Michael Lipsky's street level bureaucrat conceptual framework to explore the exercise of discretion in frontline homelessness service delivery. It is the first to apply Lipsky's model to English homelessness services at the outset, and builds on earlier investigations which have uncovered how the use of illegitimate discretion can potentially lead to detrimental outcomes for service users affected by homelessness. This topic is particularly salient in light of the current politically austere climate, whereby statutory homelessness services have experienced an increase in service users, yet resources, if anything, are declining. Interview findings from twelve local authorities found evidence of unlawful discretion, which was attributed to a complex mesh of individual, intersubjective, organisational and central-led factors. However, the use of negative discretion was chiefly underpinned by higher level pressures around resource scarcity and strict targets.